« Much Ado about Nothing » : Le passage amazonien entre le Pacifique et l’Atlantique au XVIIe siècle - Décio de Alencar Guzmán (Nuevo mundo - Mundos Nuevos, 2020)
In the Sixteenth and Seventeenth centuries, Spaniards and Portuguese sought to create a passage between the Pacific and Atlantic oceans through the Amazon region. These various projects encountered obstacles of all kinds: the Dutch maritime expansion in South America and the military and economic crisis of the Spanish empire. The project of an Amazon passage will not succeed; it will remain a dream that would be pursued until today.